THEORETICAL BASIS OF CONTROL: FOREIGN AND DOMESTIC EXPERIENCE - TYURINA, Nila; NAZARCHUK, Tatiana; HURNYTSKYI, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The importance and development of controlling in foreign countries and the reasons for its insufficient implementation at domestic enterprises are determined. The theoretical development of the basics of controlling by the authors of the German school of business administration is considered. An analytical study of the essence of the "controlling" category was conducted by foreign and domestic scientists. It was concluded that the coordination of the management system with the help of controlling is its main and predominant goal at foreign enterprises. It is established that controlling is considered as a purposeful system of planning and control, definition of goals and internal consulting. It was determined that controlling is interpreted as a management system of the process of achieving the final goals and results of the enterprises, as a cross-functional management tool that contributes to the process of making management decisions with the help of purposeful processing and supply of information. It has been investigated that the practical use of controlling in the system of effective management of the enterprise is realized with the use of appropriate methodological tools. The diversity of the use of controlling in the functional areas of enterprise activities related to: anti-crisis management, economic security, formation of the foundations of financial controlling, innovative management, strategic management is determined. A meaningful description of the theoretical basis of the controlling system has been formed.